Cooking app engages kids as well as moms: Inviting secondary users into health outreach. (February 2022) - Clarke, Peter; Neffa-Creech, Deborah; Evans, Susan H
Objective: Health apps for smartphones have largely overlooked one means of expanding effectiveness: namely, inviting access by secondary app users who can contribute positively to primary users' lives. We report on outcomes from field testing a cooking app where dissemination included both mothers who were household cooks (primary users) and their children (secondary users). Setting and Method: The app, VeggieBook, aimed to increase the use of vegetables in meals and snacks by household cooks. Clients at 15 community pantries were randomly assigned to receive or not receive the app. The same vegetables were supplied to all participants. In each family in the experimental group, the mothers and a 9- to 14-year-old child were each given their own portal into the app. Interviews before, during and after the project and electronic capture of app use measured key variables. The app's impact on children was gauged by whether or not they became involved in helping prepare family dinners. Results: Availability of VeggieBook increased children's collaboration with their mothers, even though the app contained scant content urging this. Collaboration occurred most often in families where electronic media (television, phones, earbud devices) did not intrude on socialising during meals, and there were opportunities to acknowledge children's kitchen contributions. Conclusion: Implications are identified for the creation of other health apps intended for disease prevention and management. Secondary users (spouses, home caregivers, children and friends) could also be targeted to use apps meant for primary users (people at-risk for illness or patients), thereby building collective action towards improving health.